Low cost solar ECG with Bluetooth transmitter - Parin, Dedhia; Harsh, Doshi; Mrunal, Rane; Govinda, Ahuja (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/